Kids educational and entertainment mobile application - Foong, Ling Yee (2024)
In this project, the kids' educational and entertainment mobile application is developed to help kids between 3 to 6 years old learn English and Mathematics. This app can help them to learn more effectively and flexibly because it is not similar to traditional education which has the schedule and specific location needed. Besides, there are three problem statements which are lack of flexibility while learning in traditional education mode, lack of interactivity while learning in traditional education mode, and lack of progress report. For the first problem statement, the traditional education model is lack flexibility because children need to follow the schedule and need to go to school then only can learn knowledge. They need to follow the timetable planned by the school and are not able to choose the subject they want to learn at a specific time. Therefore, one of the objectives of this project is to help children to learn more flexibly. Children can use this learning app to learn without the need to follow the timetable and they can choose the subject they want to learn. Furthermore, the second problem is there is a lack of interactivity in traditional education. This is because traditional education focuses on theory-based lessons. There is less engagement for all children to participate in learning. Thus, to solve this problem, the project objective is to increase the interactivity level in learning. This mobile app can solve this problem by letting children learn in a more interactive way such as by letting them click the letter, word, and number. Then the app will provide the sound for them to teach them how to read it. Besides, children can click the answer for the quiz. Moreover, the third problem statement is lacking a progress report. Most of the existing systems lack progress reports. Parents are not able to know the quiz result and track the progress of learning of their children. So, this application will include a progress report to record the result and the lessons learned by the children. Parents can check the application progress report to know which subject or lessons their children are currently learning.